2018
DOI: 10.1111/head.13460
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Markers of Carotid Atherosclerosis in Middle‐Aged Women: A Cross‐Sectional Study

Abstract: Objective This study evaluated the association between migraine and the markers of carotid artery disease. Background Migraine increases the risk of cardiovascular events, but its relationship with vascular dysfunction is unclear. Methods In this cross‐sectional study, middle‐aged women with no known cardiovascular diseases underwent clinical, neurological, and laboratory evaluations; pulse wave velocity (PWV) assessment; and carotid artery ultrasonography. We divided the participants based on the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…In migraineurs with subclinical infarction in the CAMERA study, the clinical and radiological features of the multiple, small lesions found predominantly in the deep arterial border zone of the cerebellum suggested hypoperfusion or embolism rather than atherosclerosis 38 . In contrast, there are 7 studies reporting evidence of subclinical atherosclerosis in adults with migraine, 136‐142 including in those with episodic migraine and those with aura 136‐139 . One recent study also reported an independent association of carotid wall thickening with triptan and ergotamine consumption, suggesting that repeated use of these vasoconstrictive agents may have lasting effects 137 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 96%
“…In migraineurs with subclinical infarction in the CAMERA study, the clinical and radiological features of the multiple, small lesions found predominantly in the deep arterial border zone of the cerebellum suggested hypoperfusion or embolism rather than atherosclerosis 38 . In contrast, there are 7 studies reporting evidence of subclinical atherosclerosis in adults with migraine, 136‐142 including in those with episodic migraine and those with aura 136‐139 . One recent study also reported an independent association of carotid wall thickening with triptan and ergotamine consumption, suggesting that repeated use of these vasoconstrictive agents may have lasting effects 137 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 96%
“…Additional causes of stroke that may be involved in migraine include enhanced cortical spreading depolarization, endothelial dysfunction, vasospasm, and coagulopathy 1 . On the other hand, arguments for a lower susceptibility to LAA in migraine are: the persistence of a strong negative association between migraine and LAA after adjustment for vascular risk factors in our study; and the results of studies in the general population that have shown less arterial calcification in the intracranial carotid artery 19 and less plaque in the extracranial carotid artery, 20 or a less pronounced tendency for extracranial carotid atherosclerosis in people with migraine than people without migraine 21 . Moreover, genome‐wide association studies have identified a single mononucleotide polymorphism of the gene PHACTR1 shared by both migraine and coronary artery disease but in an opposite direction, that is, the migraine‐associated variant was negatively associated with coronary artery disease 22,23 …”
Section: Discussionmentioning
confidence: 48%
“…In future, we will take this into consideration and exclude these confounding factors. Third, recent studies have suggested that migraine with aura is associated with an increased risk of carotid thickening, whereas migraine without aura is associated with a low risk of carotid plaques and arterial stiffening [52]. In the present study, we did not evaluate the relationship between migraine and the markers of vascular damage.…”
Section: Fig 2 Age At Onset In Patients With and Without A Family Himentioning
confidence: 71%